Blood and Site of Disease Inflammatory Profiles Differ in Patients With Pericardial Tuberculosis and Human Immunodeficiency Virus Type 1. (9th March 2023) - Mutavhatsindi, Hygon; Du Bruyn, Elsa; Ruzive, Sheena; Howlett, Patrick; Cerrone, Maddalena; Sher, Alan; Mayer-Barber, Katrin D; Barber, Daniel L; Ntsekhe, Mpiko; Wilkinson, Robert J; Riou, Catherine
Abstract: Background: To better understand the pathogenesis of pericardial tuberculosis (PCTB), we sought to characterize the systemic inflammatory profile in people with human immunodeficiency virus type 1 (HIV-1) with latent TB infection (LTBI), pulmonary TB (PTB), or PCTB. Methods: Using Luminex, we measured the concentration of 39 analytes in pericardial fluid (PCF) and paired plasma from 18 PCTB participants, and plasma from 16 LTBI and 20 PTB participants. Follow-up plasma samples were also obtained from PTB and PCTB participants. HLA-DR expression on Mycobacterium tuberculosis –specific CD4 T cells was measured in baseline samples using flow cytometry. Results: Assessment of the overall systemic inflammatory profile by principal component analysis showed that the inflammatory profile of active TB participants was distinct from the LTBI group, while PTB patients could not be distinguished from those with PCTB. When comparing the inflammatory profile between PCF and paired blood, we found that the concentrations of most analytes (25/39) were elevated at site of disease. However, the inflammatory profile in PCF partially mirrored inflammatory events in the blood. After TB treatment completion, the overall plasma inflammatory profile reverted to that observed in the LTBI group. Lastly, HLA-DR expression showed the best performance for TB diagnosis compared to previously described biosignatures built from soluble markers. Conclusions: Our results show that the inflammatory profile in blood was comparable between PTB and PCTB. However, at the site of infection (PCF), inflammation was significantly elevated compared to blood. Additionally, our data emphasize the potential role of HLA-DR expression as a biomarker for TB diagnosis.